'Nothing ruins writers like journalism': Colette, the press and belle époque literary life. (February 2015) - Dubbelboer, Marieke
This article takes Colette as a case study to explore the role of the press in the literary world of the belle époque. Like Colette, many literary authors worked in journalism, a commercial career that often clashed with ideals of creative autonomy and genius. Yet the close connection between the literary world and the press was more complex and productive than has previously been acknowledged by either cultural historians and historians of the press. This analysis offers new perspectives, not only by examining Colette's overlooked journalistic career, but also by looking at the role of money, publicity and how the press shaped the politics and poetics of writers. This paper argues that the press played a crucial and under-examined role in French literary life of the belle époque and that the study of the press contributes to a better understanding of the institutional context of cultural production.